Fraternal Twin Tumours of the Oesophagus and Stomach Presenting in the Advanced Stage – A Rare Case with a Fatal End - Sreeram, Saraswathy (J Clin Diagn Res, 2017)
Synchronous primary tumours of the aerodigestive tract presenting with different histologies is a very rare event. A case with such an association is presented here. A 50-year-old lady presented with symptoms of abdominal obstruction like abdominal pain, distention and vomiting since one month. Her radiological imaging and biopsies revealed a primary oesophageal squamous cell carcinoma and primary gastric adenocarcinoma. Western medical literature has shown the occurrence of multiple synchronous cancers; however, cases from India have seldom been reported. Early screening, correct diagnosis and appropriate plans of management are crucial to reduce the morbidity and mortality of such patients who bear the burden of not just one, but multiple primary cancers.